In-situ construction of novel naphthalenediimide/metal-iodide hybrid heterostructures for enhanced photoreduction of Cr (VI). (March 2021) - Li, Meng-Hua; Di, Yi-Ming; Wang, Yi-Wen; You, Ming-Hua; Lin, Mei-Jin
Abstract: The organic-inorganic donor-acceptor (D-A) hybrid heterostructures, an emerging class of hybrid complexes containing semiconductive organic dyes and inorganic pigments at a molecular level, have displayed extraordinary optoelectronic properties and applications. Herein, we demonstrated that the combination of dipyridyl-naphthalene diimide tecton (DPNDI) with CuI (or AgOOCF3 ) resulted in two isostructural D-A hybrid heterostructures based on 1D [Cu8 I14 ] 6- or [Ag8 I14 ] 6- polyanions surrounded by an interwoven network of in situ N -methylated DPNDI cations. Due to the compact contact between these two semiconductive components by the charge-assisted anion-π and C–H⋯I hydrogen-bonding interactions, the obtained hybrid materials not only display high chemical stability but also exhibit high efficiency and moderate stability in the photoreduction of Cr(VI) upon visible light irradiation. The influences of various experimental conditions on the photocatalytic reactions including pH value and hole scavenger have been investigated. In addition, the possible mechanism studied shows that photogenerated electrons are the main active substances in the photoreduction of Cr(VI). This study suggests that constructing D-A hybrids heterostructures by two functional components with noncovalent interactions are promising for developing the hybrids used in the reduction of Cr(VI) in the future. Graphical abstract: Two isomorphic D-A hybrid heterostructures based on 1D [Cu8 I14 ] n 6n- or [Ag8 I14 ] n 6n- polyanions and interwoven networks of in-situ N -methylated DPNDI cations exhibit high efficiency towards the photoreduction of Cr(VI). Image 1 Highlights: Two isomorphic D-A hybrid heterostructures have been synthesized. Both heterostructures are composed of 1D metal-iodide polyanions and an interwoven network of N- methylated DPNDI cations. The obtained hybrid materials exhibit highly efficient in photoreduction of Cr(VI) under visible light irradiation. The influence of various factors on the photocatalytic reactions and possible mechanism have been investigated. This study suggests that such unique D-A hybrids are promising photocatalysts for the reduction of Cr(VI) in wastewater.